Altered Homeostasis of Systemic Glucocorticoids as Related to Obesity, Glucose Tolerance, and Smoking - Schäfer, H. H.; de Villiers, J. D.; Sivukhina, E.; Lewis, J.; Wande, D.; Perembe, B.; Jirikowski, G. (Hormone and Metabolic Research, 2013)
The hypothalamic-pituitary-adrenal axis is supposed to be involved in the pathogenesis of the metabolic disorders. Differences in adipose tissues and parameters of insulin resistance are linked to steroid homeostasis. We assessed the correlation of fat tissue distribution, gender, and glucose control with levels of systemic corticosteroid-binding globulin (CBG), free cortisol (FuF), and total cortisol (FuM). Data of 1 114 patients with overweight, lipid disorders, and impaired glucose tolerance were collected. Blood samples were sorted according to gender and anthropometric measures. Variable-association was calculated using the Spearman Rank Correlation coefficient and tested for significance (p<0.05 and p<0.01). CBG and FuF were consistently negatively correlated to each weight parameter. Especially in women, fat mass index (FMI) was significantly negatively correlated with CBG-levels. While CBG levels dropped with increasing age, FuF showed an inverse behavior. Glycohemoglobin levels showed negative correlations with CBG while fasting glucose did not. Both changes were associated with significant increases in FuF. All negative correlations to cortisol and its binding globulin with regards to weigh- and glucose-control parameters were absent in smokers compared to nonsmokers. Our observations suggest that different weight parameters correspond to adrenal steroids and their buffer systems. Especially in women, CBG levels might serve as prognostic marker for the fat mass. In addition, CBG levels may predict long term blood glucose control more reliably than FG. However, the value of CBG as an indirect surrogate-marker for obesity and glucose is limited in smokers.
Keywords: CBG; cortisol; HPA axis; body weight